2011
DOI: 10.1128/mcb.00740-10
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling of HMGN1 Reveals an Association with Chromatin at Regulatory Regions

Abstract: The interaction of architectural proteins such as the linker histone H1 and high-mobility-group (HMG) proteins with nucleosomes leads to changes in chromatin structure and histone modifications and alters the cellular transcription profile. The interaction of HMG proteins with chromatin is dynamic. However, it is not clear whether the proteins are constantly and randomly redistributed among all the nucleosomes or whether they preferentially associate with, and turn over at, specific regions in chromatin. To ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 59 publications
6
58
0
Order By: Relevance
“…Genomic profiling of human CD4ϩ T cells revealed that HMGN1 preferentially localizes to chromatin regulatory sites and to promoters of transcriptionally active genes (22), a finding that is in full agreement with its widespread effects on the cellular transcription profile (14). Among the regulatory sites bound by HMGN1 is the promoter of the gene coding for methyl CpG-binding protein 2 (MeCP2), a nuclear protein that is expressed postnatally during mammalian brain development and is highly abundant in neurons (23).…”
Section: Hmgn1mentioning
confidence: 65%
See 4 more Smart Citations
“…Genomic profiling of human CD4ϩ T cells revealed that HMGN1 preferentially localizes to chromatin regulatory sites and to promoters of transcriptionally active genes (22), a finding that is in full agreement with its widespread effects on the cellular transcription profile (14). Among the regulatory sites bound by HMGN1 is the promoter of the gene coding for methyl CpG-binding protein 2 (MeCP2), a nuclear protein that is expressed postnatally during mammalian brain development and is highly abundant in neurons (23).…”
Section: Hmgn1mentioning
confidence: 65%
“…Anti-␤-actin mouse monoclonal, catalog #A5316 clone AC-74, anti-human HMGN1 (62,63), and anti-mouse HMGN1 (peptide 6) (12, 64) were from Sigma. ChIP sequence analysis of CD4ϩ human T cells was performed as described (22). All antibodies were used for chromatin immunoprecipitation except for anti-MeCP2 and anti-␤-actin, which were used for Western blot.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations